Faktor-faktor yang Berhubungan dengan Sisa Makanan pada Pasien Bedah di Ruang XX - Regina Wihelsha; Eka Roshifita Rizqi; Wanda Lasepa (Science: Indonesian Journal of Science, 2025)
Large amounts of food waste over a long period of time cause nutritional deficiencies that slow down healing. The purpose of this study was to determine the factors associated with food waste in surgical patients in the Xs Room of X Hospital. This type of research is quantitative research with cross-sectional design using purposive sampling technique as many as 136 samples. Data were collected using a questionnaire. The analysis used was univariate and bivariate analysis (Chi Square test). Of the 136 respondents, as many as 73 respondents (53.7%) had a lot of food left, as many as 78 respondents (57.4%) the taste of food was not appropriate, as many as 76 respondents (55.9%) the appearance of food was not attractive and as many as 79 respondents (58.1%) often ate food from outside the hospital. Based on the results of statistical tests there is no relationship between Food Taste (p value = 0.062), there is a relationship in Food Appearance (p value = 0.001) and Food from Outside the Hospital (p value = 0.013) with Leftover Food for Surgical Patients. The study concluded that there was no relationship between food flavour and food waste, and there was a relationship between food appearance and consuming food from outside the hospital with food waste. This study is expected as additional knowledge for patients and families to increase awareness of the importance of food provided by the hospital.